(untitled) (Education in the 21st Century, 2023)
The article seeks to understand the intricate nature of listening comprehension, which depends to a great extent on the specific features of spoken language. It proves that the effective listening process requires definite skills (recognition, identification, and selection), and different types of knowledge. The obtained results indicate that the ways of processing the incoming information fall into two broad categories: bottom-up and top-down. The former implies using knowledge about sounds and word meanings, which helps to assemble the understanding of what the learner hears. The latter derives from utilizing the listener’s prior knowledge and his own experiences to comprehend the received input. The paper reveals that the combination of extensive and intensive types of listening proves fruitful in teaching oral comprehension. With the intention to demonstrate the practical validity of the suggested theoretical grounds, the relevant methodology of shaping listening comprehension competence is devised. The idea is maintained that processing the audio text encompasses three stages, each of which has to be provided with a set of relevant exercises which aim at simulating real-life communication.